1977
DOI: 10.1007/bf00223111
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, ontogeny and ultrastructure of the mammalian secretin cell

Abstract: Immunocytochemically, secretin cells have been demonstrated to occur in the duodenum and jejunum of several mammals. Calculations on the relative frequency of such cells indicate that the bulk of secretin occurs in the jejunum, a fact supporting the view that secretin may be released by physiological stimulants other than hydrochloric acid. Electron microscopical identification of cat and pig secretin cells confirmed their identity with the ultrastructurally defined S cells, and staining experiments revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In most species, secretin cells are present in highest abundance in the proximal small intestine and decrease distally in the jejunum, ileum, and colon. Secretin cells are found in villi and zones of transition between villi and crypts of the intestinal epithelium (25). In the rat, Northern (RNA blot) analysis confirmed that the small intestine was the primary site of secretin gene expression (23).…”
mentioning
confidence: 80%
“…In most species, secretin cells are present in highest abundance in the proximal small intestine and decrease distally in the jejunum, ileum, and colon. Secretin cells are found in villi and zones of transition between villi and crypts of the intestinal epithelium (25). In the rat, Northern (RNA blot) analysis confirmed that the small intestine was the primary site of secretin gene expression (23).…”
mentioning
confidence: 80%
“…The 28 amino acid peptide VIP is presumed to occur in neurones in the gut and pancreas and it has been suggested to be a neurotransmitter [10][11][12][13] amino acid peptide secretin has been shown to occur in endocrine cells in the small intestine [14]. Chemically VIP and secretin resemble glucagon and GIP, and these polypeptides have been grouped in one family [5].…”
Section: Discussionmentioning
confidence: 99%
“…Our antibodies could not visualize secretin-immunoreactive cells. This was proba bly caused by the fixative technique used in the present study [36],…”
Section: Fig 3 Photograph O F Duodenal Sections Showing Serotonin-imentioning
confidence: 98%